Didactic Values and Cultural Expressions of the Minangkabau Community Prohibition in Nagari Biaro Gadang - Hafizah Hafizah; Zuriyati Zuriyati; Ninuk Lustyantie (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to determine the didactic value and cultural value of the expression of prohibition used by the Minangkabau community in Nagari Biaro Gadang, Agam Regency, West Sumatra. This research method used descriptive qualitative method and was carried out in three stages, such as data collection, data classification, and data analysis stages. The data was collected by observing, interviewing, recording, and taking notes on the utterances conveyed by the informants. Classification of data was done by collecting forbidden expressions. Prohibition expressions are analyzed by using a hermeneutic approach to find out the meaning of the existing prohibition expressions. Analyzing data by transcribing the results of interviews, translating into Indonesian, grouping prohibition expressions based on didactic values consisting of religious education values, moral education values, and social education values and cultural values in forbidden expressions. The result of the research shows didactic values, which consist of religious education, moral education, and social education. In addition, in the expression of the prohibition of the Minangkabau people of Nagari Biaro Gadang, cultural values are also found. The conclusion of this research is that each prohibition expression had its own didactic and cultural values.Keywords: Prohibition Phrases, Didactic and Cultural Values, Minangkabau Cultures.